Autobiography, Time and the Palimpsest in Jamaica Kincaid’s See Now Then: A Novel - Bárbara Arizti (Anglica. An International Journal of English Studies)
This article analyses Jamaica Kincaid’s autobiographical novel See Now Then through the metaphor of the palimpsest with the aim of exploring the frictions between the different generic and thematic layers that make up the text. It argues that despite the novel’s generic openness, its thematic concerns, most notably its treatment of time and narrative temporality, encourage a backward-looking stance that reasserts the past. The theories of Sarah Dillon and Lene Johannessen on the nature of palimpsests, especially the difference between the palimpsestic and the palimpsestuous and the interaction between the horizontal and the vertical, the new and the old, will be drawn upon in conjunction with Leigh Gilmore’s investigations into limit case autobiographies – works, like Kincaid’s, that question the borders between fiction and life-writing under the pressure of traumatic experiences.